Pelatihan dan Pendampingan Teknik Penyusunan Peraturan Kampung di Distrik Muara Tami, Kota Jayapura - Kambuaya, Ruth; Reumi, Ludia J.I.; Mulyadi, Dudi; Yanuaria, Tri (Bakti Hayati: Jurnal Pengabdian Indonesia, 2025)
Based on the results of training on Techniques for Preparing Good Village Regulations, it was found that there are still many village officials (Village Heads and Village Consultative Body) who do not have the knowledge and expertise in drafting good village regulations in accordance with the provisions of statutory regulations. The low level of knowledge of village government officials in drafting village regulations has created a legal vacuum in society, thereby affecting the effectiveness of village government administration. If this is not addressed from the start, it can affect all village development policies in accordance with the mandate of Law Number 6 of 2014 concerning Villages. The objectives of training in preparing good village regulations are (1) to provide knowledge and understanding of the procedures for preparing good and correct village regulations (2) to provide knowledge about the correct preparation of village regulations in accordance with the theory, principles and concepts of legislative science. The expected benefit from training in techniques for preparing good village regulations is that it can provide scientific contributions to village government officials and the community regarding the benefits of correct procedures for drafting village regulations and how to implement the village regulations themselves. Community service was carried out in Skouw Mabo Village, Muara Tami District, Jayapura City using the method: lectures and discussions with the theme "Training on Techniques for Preparing Good Village Regulations for Village Government Apparatus", then continued with a question and answer session to explore the problems and obstacles faced and find solutions as a form of resolving the obstacles faced by village government officials. Based on the results achieved in this training activity, it can be concluded as follows: (1) training participants are able to understand and know the procedures for preparing village regulations that are good and correct; and (2) and Training Participants can apply the results of the training by compiling and implementing village regulations independently